Robust nanoscale contact of silver nanowire electrodes to semiconductors to achieve high performance chalcogenide thin film solar cells. (November 2018) - Lee, Sangyeob; Lee, Jun Su; Jang, Jiseong; Hong, Ki-Ha; Lee, Doh-Kwon; Song, Soomin; Kim, Kihwan; Eo, Young-Joo; Yun, Jae Ho; Gwak, Jihye; Chung, Choong-Heui
Abstract: We demonstrate the ability to fabricate high-quality nanoscale electrical contact between silver nanowires (AgNWs) and underlying semiconducting layers in chalcogenide thin film solar cells. AgNW electrodes have attracted many interests due to their ability for low temperature solution processing. However, they have a drawback that the interfacial defects can be generated between AgNWs and underlying rugged semiconductor layers making it difficult to form high-quality junction. To enhance the junction properties, conducting matrix layers have been adapted. Yet, the issues regarding the AgNW/semiconductor junction have not been fully resolved. We developed a facile method to form robust nanoscale contact between AgNWs and semiconducting thin films to achieve high performance chalcogenide thin film solar cells. The method is to deposit an ultra-thin semiconductor layer on devices using aqueous chemical bath deposition. The chemical bath deposition has capability to effectively fill even nanoscale gap and to form chemically stable bonds as well as an intimate junction. As a proof of concept, a CdS layer ( 10 nm) was deposited using the chemical bath deposition on Cu(In, Ga)Se2 (CIGS) solar cells with a structure of AgNW/CdS/CIGS/Mo/Glass. We also identified that the key factor governing the current-voltage characteristic is the electrical contact between the AgNW electrode and the CdS buffer layer in CIGS thin film solar cells. The power conversion efficiency of the CIGS cell was dramatically improved from 4.9% to 14.2% owing to high-quality AgNW-CdS electrical contact produced by chemical bath deposition of the additional CdS layer as thin as 10 nm. Graphical abstract: fx1 Highlights: A facile method to form robust nanoscale contact between AgNWs and semiconductors for high performance solar cell. Formation of high quality junction between AgNWs and a CdS buffer layer in CIGS solar cells by chemical bath deposition. Due to the high quality contact, the efficiency of CIGS solar cells dramatically improves from 4.9% to 14.2%. The cells with high quality junction show high performance at any illumination conditions.